Risk of recurrence in patients with pulmonary embolism: Predictive role of D-dimer and of residual perfusion defects on lung scintigraphy - Poli, Daniela; Cenci, Caterina; Antonucci, Emilia; Grifoni, Elisa; Arcangeli, Chiara; Prisco, Domenico; Abbate, Rosanna; Miniati, Massimo (Thrombosis and Haemostasis, 2013)
The stratification of recurrence risk after a first episode of venous thromboembolism (VTE) is an important topic of research, especially in patients with pulmonary embolism (PE). Elevated D-dimer levels and residual vein obstruction (RVO) at compression ultrasonography have been studied as predictors of recurrence after withdrawing oral anticoagulant treatment (OAT). It is still unknown if residual perfusion defects (PD) on lung scintigraphy are related to recurrent PE. In the present study, we evaluated the association of PD with PE recurrence. The relationship between PD, elevated D-dimer levels, and RVO was also investigated. We prospectively followed 236 consecutive patients who survived a first episode of objectively confirmed PE, with or without deep-vein thrombosis. After at least three months of OAT, treatment was withdrawn in 139 patients. D-dimer levels were evaluated at one month of OAT withdrawal, RVO was measured, and perfusion lung scan (P-scan) was performed to evaluate PD. During follow-up, 20 patients experienced a recurrent episode of VTE. Elevated D-dimer levels were significantly associated with VTE recurrence, (p=0.003). RVO was present in 22% of the patients with recurrence and in 7.5% of those without (p=0.07). No significant association was found between PD >10% and VTE recurrence, D-dimer, or RVO. In conclusion, we confirmed the positive predictive value of elevated D-dimer levels for recurrent VTE. Residual PD on lung scintigraphy are neither predictive of recurrence nor related to D-dimer levels or RVO.
Keywords: D-dimer; perfusion defects; pulmonary embolism; recurrence